PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK KELAS X-IPA3 MAN 1 JEMBRANA DENGAN PENGGUNAAN MEDIA UNSURE CARD AND ZERO UNSURE PERIODIC TABLE DARI BAHAN LIMBAH - HENDAH TRI SULYANTARI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
The low grades of students and the mastery of student learning on the results of the initial test of the atomic structure material caused the writer to want to change the learning method so as to achieve the maximum value. The method chosen is the development of the Cooperative Learning method with card media. The results of the treatment cycles 1 and 2 there was an increase in the pretest and posttest in the evaluation of learning outcomes as a whole for the chapter. This shows that practicing questions in any way as long as students are comfortable can improve student learning outcomes. Cycle 1 of card elements is used to discuss questions, the average value is still low, because the questions asked are considered difficult. This happens because students do not understand the material being taught, students are given the opportunity to ask questions, students in presenting the material there are still wrong concepts so that the teacher improves the concept. In cycle 1 the teacher has not given discussion paper so that the discussion directions are messy and the size of the presentation sheet is too small. Cycle 2, card game elements, zero periodic table elements and discussion paper zero periodic table elements. There was an increase in the post test scores from cycle 1 to cycle 2 an average of 93 to 96. The questions refer to the standard questions. The material asked is evenly distributed, this seems easier. Completeness of student learning results post 100% in cycle 1 and cycle 2. Student absorption from cycle 1 to cycle 93.21% increased 96.13% ABSTRAKRendahnya nilai siswa dan ketuntasan belajar siswa pada hasil tes awal materi struktur atom menyebabkan penulis ingin merubah metode belajar sehingga mencapai nilai maxsimal. Metode yang dipilih pengembangan metode Cooperative Learning dengan media kartu. Hasil perlakuan siklus 1 dan 2 terjadi peningkatan pretest dan postest pada evaluasi hasil belajar secara keseluruhan bab tersebut. Hal ini menunjukkan bahwa berlatih soal dengan hal apapun asal siswa nyaman dapat meningkatkan hasil belajar siswa. Siklus 1 unsure card digunakan untuk membahas soal, nilai rerata masih rendah, karena pertanyaan yang diajukan dianggap sulit. Hal ini terjadi karena siswa belum paham dengan materi yang diajarkan, siswa diberi kesempatan bertanya, siswa dalam mempresentasikan materi masih ada salah konsep sehingga guru memperbaiki konsep. Pada siklus 1 guru belum memberikan kertas diskusi sehingga pengarahan diskusi berantakan dan lembar presentasi ukuran terlalu kecil. Siklus 2, permaian unsure card, zero unsure periodic table dan kertas diskusi zero unsure periodic table. Terjadi peningkatan nilai post test dari siklus 1 ke siklus 2 rerata 93 menjadi 96. Soal mengacu pada stándar soal. Materi yang ditanyakan merata, hal ini terkesan lebih mudah. Ketuntasan belajar siswa hasil post 100 % pada siklus 1 dan siklus 2. Daya serap siswa dari siklus 1 ke siklus 93,21 % meningkat 96,13 %